What's your presentation persona? : discover your unique communication style and succeed in any arena - Schwertly, Scott; Mancini, Sunday (McGraw Hill-Ascent Audio, 2017)
A practical guide based on a proprietary skill assessment tool-a Myers-Briggs for presenters-that provides tips and strategies that address the core element for becoming a successful presenter: YOU What kind of presenter are you? Are you charming? Purposeful? Informative? Inspiring? Do you have natural charisma? A clear message? A powerful vision? What's Your Presentation Persona? is a revolutionary guide based on Badge, the first-of-its-kind proprietary skill assessment tool-a Myers-Briggs for presenters-that provides strategies and tips that address the core element for becoming a successful presenter: YOU. This groundbreaking book identifies 16 presentation personas, each with its own strengths and weaknesses, and shows you how to leverage your unique qualities to become a more powerful, persuasive, and successful presenter. Take the self-assessment test in the book and discover your persona. Are you: * The Director: a respected leader with an empathetic core (Oprah Winfrey or Ned Stark from Game of Thrones) * The Captivator: a charismatic presenter with a natural, unrehearsed flair (Gary Vaynerchuk or Captain Kirk from Star Trek) * The Producer: a successful speaker who believes in hard work-not luck (Martin Luther King Jr. or Walter White from Breaking Bad) * The Scholar: an always-curious learner informed by their own wisdom (Elon Musk or Hermoine Granger from Harry Potter) * The Liberator: an optimistic visionary who loves to inspire (Tony Robbins or William Wallace from Braveheart) The key to reaching others is knowing who you are. Get to know yourself. Build on your strengths. Work on your weaknesses. Learn how to deliver your message with confidence, charisma, humor, and authenticity. Be yourself-but better. Once you've mastered your presentation persona, explore others you'd like to experiment with and learn from. Incorporate techniques into your unique style to become the strongest, most well-rounded communicator you can be-so you can razzle-dazzle any audience on any topic anytime.